Androgen receptor signaling–mitochondrial DNA–oxidative phosphorylation: A critical triangle in early prostate cancer. (31st December 2022) - Sakellakis, Minas; Flores, Laura Jacqueline
Abstract: Mitochondria are more than just the cellular powerhouse. They also play key roles in vital functions such as apoptosis, metabolism regulation, and other intracellular interactions. The mitochondrial DNA (mtDNA) encodes for 12 subunits of the oxidative phosphorylation (OXPHOS) system. Depletion of mtDNA in androgen-dependent prostate cancer (PCa) cell lines renders them androgen-independent and more aggressive. Paradoxically, pharmaceutical inhibition of OXPHOS is lethal for subsets of PCa cells, whereas others become dependent on androgen receptor (AR) signaling for survival. Given that the AR-mitochondria interaction is critical for early PCa, it is crucial to understand the details of this interaction. Technical hurdles have made mitochondria traditionally difficult to study, with many techniques used for isolation masking the properties of given individual mitochondria. Although the isolation of mitochondria enables us to study OXPHOS, we miss the context in which mitochondria interact with the rest of the cell. Both AR signaling and mtDNA affect apoptosis, metabolism regulation, cellular calcium storage and homeostasis, intracellular calcium signaling, and redox homeostasis. In this review, we will attempt to understand how the crosstalk between AR-mtDNA-OXPHOS is responsible for "life or death" decisions inside the cells. Our aim is to point toward potential vulnerabilities that can lead to the discovery of novel therapeutic targets.